Strategic Intervention Material in English 6 (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
The use of strategic intervention material (SIM), both an instructional and an intervention strategy, has been prescribed by the Department of Education to improve the performance of students in the different areas as the use of SIM is believed to be an effective strategic teaching aid for teachers to empower learners to curb the least-mastered competencies. The preceding situation inspired the conduct of this study to assess the effectiveness of a developed strategic intervention material in the development of the English competencies of the Grade 6 learners of Pao Elementary School during the SY 2019-2020. This study employed the one-shot pre-test-post-test design to determine the least-mastered competencies. The researcher utilized the mean percentage score and weighted mean in finding the level of competence along with the indicators and paired samples t-test to determine the significant difference in the English competencies before and after the intervention. The results showed that the respondents registered low mastery in the identified competencies and moving towards mastery after the intervention. Furthermore, it was noted that a significant difference was established between the pre-test and post-test results of the respondents on the competencies studied. This is a manifestation that the respondents' English competence improved after the use of the intervention material in the respondents' English class. Although considering several limitations, the findings established the intervention material's effectiveness in addressing the least mastered competencies of Grade 6 learners in English; thus, the researcher recommends its adoption by teachers of the English subject for sixth graders.
Keywords: strategic intervention material, English competencies